2022
DOI: 10.18844/wjet.v14i4.7729
|View full text |Cite
|
Sign up to set email alerts
|

Technology integration in learning management: A post-pandemic phenomenological study in elementary schools

Abstract: The post-pandemic period in the education sector is marked by government policies to carry out face-to-face education processes in schools. This situation has the potential to show various changes in learning management in elementary schools, especially with the integration of technology. This study aims to analyse the integration of technology in learning management in elementary schools during the post-pandemic period. This study uses a qualitative approach to the type of phenomenology. The research subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The integration of technology in learning management is very important to keep up with the times (Ilyas et al, 2022). All components of education should adapt to technological developments, including parents in accompanying their children to study at home (Herwin & Dahalan, 2022a).…”
Section: Figure 1 Login Page Of the Learning Management Systemmentioning
confidence: 99%
“…The integration of technology in learning management is very important to keep up with the times (Ilyas et al, 2022). All components of education should adapt to technological developments, including parents in accompanying their children to study at home (Herwin & Dahalan, 2022a).…”
Section: Figure 1 Login Page Of the Learning Management Systemmentioning
confidence: 99%
“…Previous literature has suggested that technological integration can enhance children's learning interest, offering diverse media displays to maintain attention and mitigate boredom [6]. This principle holds true in Indonesia's postpandemic educational landscape, where technological applications in learning activities are frequently discussed in both academic and practical educational contexts [7].…”
Section: Introductionmentioning
confidence: 99%
“…The problem faced by students after the pandemic is the problem of interest in learning and enthusiasm to return to study in normal situations [13][14][15][16]. Students seem not yet fully able to adjust the transition period after distance learning and then move to face-to-face meetings in class [17]. This has an impact on learning outcomes that have not been satisfactory and have not met expectations.…”
Section: Introductionmentioning
confidence: 99%